Unravelling the mystery of parole in China - Li, Enshen (The British journal of criminology, 2022)
Across a burgeoning literature on punishment and society, the subject of parole has mostly been in the shadows of the disproportionate scholarly attention drawn to imprisonment. This article offers the first analytical examination of parole in China by addressing the fundamental question—why has early prison release been an underused instrument in the Chinese penal system for decades? By reflecting on the sociological perspective of punishment, my discussion situates Chinese parole in the wider sociopolitical context of penal development in order to reveal its distinctive position, structure and character within China’s criminal justice system. Using existing data publicly available and judicial parole decisions from China Judgments Online, this article posits that China’s parole system is devised primarily as a punitive preventive measure to control the release of prisoners back into society. Rather than being rehabilitative and re-integrative, parole is operationalized to incapacitate as well as punish those deemed dangerous with a (high) risk of recidivism.